Exploring The Economic Potential of Banjararum Village Through Economics Education: A Phenomenological Analysis - Ardhita Eko Ginanjar; Waspodo Tjipto Subroto; Muhammad Abdul Ghofur; Heny Musfidah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
Banjararum Village in Tuban Regency, East Java, has a variety of good economic potential, unfortunately it has not been utilized optimally and is reflected in the high percentage of poor people at 30%, which is the main problem in this research. An ideal example is Karangtinoto Village in Tuban Regency which has successfully produced 7,780 tons of rice in one harvest and the rapid development of local businesses. This success is partly due to optimal training of farmers and entrepreneurs. Unfortunately, these efforts have not been evenly implemented, including in the neighboring village of Banjararum, causing massive economic inequality between the two. The aim of the research itself is to identify the village's economic potential, the role and economic impact of education in society. This research uses a qualitative phenomenology. Data collecting method were using interview, observation and questionnaire techniques, given to key informants, namely five residents with different professions to represent the economic conditions of Banjararum Village. The data analysis technique used is analysis using the Miles & Hubberman framework and triangulation. From this, the results obtained are that in the agricultural sector changes are needed in the form of training to optimize agricultural products according to the capacity of residents, while from the local business side, training is needed that focuses on the craft sector and street businesses to advance the village economy which is not yet running well.Keywords: Economics of education, Village potential, Phenomenology, Village economy